2011
DOI: 10.2514/1.j050802
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Order Aerothermoelastic Framework for Hypersonic Vehicle Control Simulation

Abstract: Hypersonic vehicle control system design and simulation require models that contain a low number of states. Modeling of hypersonic vehicles is complicated due to complex interactions between aerodynamic heating, heat transfer, structural dynamics, and aerodynamics. Although there exist techniques for analyzing the effects of each of the various disciplines, these methods often require solution of large systems of equations, which is infeasible within a control design and evaluation environment. This work prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 56 publications
(89 reference statements)
0
32
0
2
Order By: Relevance
“…The other involves the fact that K * uu (T ) and K * ur (T ) on the right-hand sides of Eqs. (5) and (14) are evaluated at the reference thermal state and held constant throughout the simulation. In order to distinguish the errors due to these approximations from the errors due to modal truncation, three different cases are simulated as shown in Table 5.…”
Section: Of 37mentioning
confidence: 99%
See 1 more Smart Citation
“…The other involves the fact that K * uu (T ) and K * ur (T ) on the right-hand sides of Eqs. (5) and (14) are evaluated at the reference thermal state and held constant throughout the simulation. In order to distinguish the errors due to these approximations from the errors due to modal truncation, three different cases are simulated as shown in Table 5.…”
Section: Of 37mentioning
confidence: 99%
“…Additionally for case E3, K * uu (T ) and K * ur (T ) on the right-hand sides of Eqs. (5) and (14) are evaluated at the reference thermal state and held constant throughout the simulation. Therefore, the difference between cases E1 and E2 will demonstrate the error incurred solely due to the use of the modal subset in the structural ROM.…”
Section: Of 37mentioning
confidence: 99%
“…์ด ๋•Œ๋ฌธ์— ๊ณต ๋ ฅ, ๊ตฌ์กฐ ๋ณ€ํ˜•์— ๋Œ€ํ•œ ์ถ•์•ฝ๋ชจ๋ธ(reduced-order model)์„ ๊ตฌ์ถ•ํ•˜๊ณ , ์ด๋“ค์„ ํ†ตํ•ฉํ•˜์—ฌ ๊ณตํƒ„์„ฑ ํ˜น ์€ ์—ด๊ณตํƒ„์„ฑ(aerothermoelastics) ํ•ด์„์„ ์ˆ˜ํ–‰ํ•˜๋Š” ๋ฐฉ๋ฒ•๋ก ์„ ์—ฐ๊ตฌํ•˜๊ณ  ์žˆ๋‹ค [1][2][3][4][5][6][7][8][9].…”
unclassified
“…ํ•œํŽธ, ๋ฏธ๊ตญ์˜ McNamara ๊ต์ˆ˜์™€ Cesnik ๊ต์ˆ˜ ์—ฐ๊ตฌํŒ€์€ Kriging ๋ฐ POD ๊ธฐ๋ฒ•์„ ์ ์šฉํ•˜์—ฌ ๊ณต ๋ ฅ, ๊ตฌ์กฐ, ์—ด์ „๋‹ฌ์— ๋Œ€ํ•œ ์ถ•์•ฝ๋ชจ๋ธ ๊ตฌ์ถ•ํ•˜๊ณ  [3][4][5][6][7], ์ด๋ฅผ ์ด์šฉํ•ด ์ดˆ์Œ์† ํ”Œ๋Ÿฌํ„ฐํ•ด์„์„ ์ˆ˜ํ–‰ํ•œ ๋ฐ” ์žˆ ๋‹ค [7][8][9]. ํŠนํžˆ ์ด๋“ค์€ ์ดˆ์Œ์† ๋น„์ •์ƒ(unsteady) ํ‘œ ๋ฉด ์••๋ ฅ ๋ถ„ํฌ๋ฅผ ์ถ•์•ฝ ๊ณ„์‚ฐํ•˜๊ธฐ ์œ„ํ•ด ํ”ผ์Šคํ†ค ์ด๋ก  ์„ ์ ์šฉํ•˜์˜€๋‹ค.…”
unclassified
“…Whereas the early research was instrumental in providing the basis for the aerothermoelastic design of the X-15 and the space shuttle [3][4][5], the current focus is on the development of hypersonic technologies for next-generation reusable launch vehicles and hypersonic cruise vehicles [6][7][8]. Current research includes: development of reduced order models for aerothermoelastic systems [9,10], structural optimisation [11], uncertainty propagation [12,13], coupling CFD with aerothermoelastic models [14], two-dimensional nonlinear flutter models [15] and three-dimensional flutter models [16]. This work has shown that the dynamic behaviour of the structure under the harsh thermal environment must be investigated for hypersonic aircraft to become a reality.…”
Section: Introductionmentioning
confidence: 99%